Extreme events: from geophysics to astrophysics - Prete, Giuseppe; Cipparrone, Gabriella; Carbone, Vincenzo (Università della Calabria, 2023)
The aim of this thesis work is the study of extreme event phenomena. Extreme events are well known in nature and they present different characteristics. They are often related to the climate effects, as extreme temperature or rainfall, but it is also possible to define them in the Heliosphere environment, such as slow or fast Coronal Mass Ejection speed events or intense Flares eruptions. Another class of phenomena that can be classified as extreme events are the explosion of Supernova. In this work these different will be analyzed types of phenomena with the help of statistical models, numerical simulations and data analysis. In the first part we will focus on the extreme events that influence the climate. In particular, we study how these phenomena characterize different world regions. In particular we will concentrate on three regions: the Antarctica continent, the Basilicata and the Calabria regions. The study will be made with the help of a statistical analysis applied on the stations data. This will allow us to make a foresting analysis on the examined regions, identifying what are the zones most affected by extreme phenomena, in order to prevent possible disasters such as floods, landslides, droughts. In the second part we will explore the nature of Heliosphere extreme events. In particular we will study a particular class of Coronal Mass Ejections defined as extreme, namely the low speed ones. We will study this category of extreme events with the help of spacecraft data and numerical simulations. Numerical simulations help to do predictions on the SpaceWeather extreme events, because they are able to reproduce a particular event and study how damaging it can be if it has some particular characteristics. Then we will make a comparison between satellite data and numerical results in order to see if the simulation developed is able to reproduce what the spacecraft detects. We will also study the transport properties of energetic particles at the interplanetary shock, analyzing the possible acceleration mechanisms that can influence the particles energization. In the last part of the thesis, we will concentrate on Galactic and extra Galactic extreme events, called Supernova explosions. We will use numerical simulations in order to reproduce the evolution of the Supernova from early stage to the final time of its evolution. We will set a turbulent and dense environment in which it can develop and we will study its evolution with different configurations. Finally we will try to make a visual comparison between numerical results and spacecraft data obtained for the Supernova Remnant SN1006.
UNIVERSITA’ DELLA CALABRIA Dipartimento di Fisica Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali. Ciclo XXXV
Keywords: Alluvioni; Temperature estreme; Teoria EVT; Espulsioni di massa coronale (CME)